2021
DOI: 10.1007/s10389-021-01497-y
|View full text |Cite
|
Sign up to set email alerts
|

Promoting social distancing and preventing panic buying during the epidemic of COVID-19: the contributions of people’s psychological and behavioural factors

Abstract: Objectives COVID-19 disease has progressed to the level of a global pandemic. This study aimed to investigate people's psychological and behavioural responses to the COVID-19 epidemic and explore the predictors for social distancing and panic buying. Methods A 17-item questionnaire was developed and distributed randomly to people using social media. Descriptive statistics and one-way ANOVA were used to assess people's psychological and behavioural responses. Hierarchical regression was conducted to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…Future studies should also ask about the purchasing of different types of products. For example, Zhang and Zhou (2021) found that perceived risk of COVID-19 was related to panic buying masks and food, though only panic buying of food was related to refusing home visitors and cancelling outings (i.e., indicators of social distancing).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should also ask about the purchasing of different types of products. For example, Zhang and Zhou (2021) found that perceived risk of COVID-19 was related to panic buying masks and food, though only panic buying of food was related to refusing home visitors and cancelling outings (i.e., indicators of social distancing).…”
Section: Discussionmentioning
confidence: 99%
“…The degree to which an individual perceives the threat or scarcity of a product is an important determinant of panic buying behaviour ( Yuen et al., 2020 ). For example, recent surveys assessing individuals from the US, China, India, and Pakistan found that greater perception of the risk and severity of COVID-19, greater news monitoring, and perceived scarcity were associated with more panic buying ( Clemens et al., 2020 ; Islam et al., 2020 ; Oosterhoff and Palmer, 2020 ; Zhang and Zhou, 2021 ). Further, when others are seen to panic buy, this may intensify the perceived scarcity of a product and increase the motivation to panic buy, resulting in herd behaviour ( Baddeley, 2010 ; Loxton et al., 2020 ; Zheng et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent review on global COVID-19 vaccine acceptance ( Salomoni et al, 2021 ), the highest rates of vaccine acceptance were reported in Asia, including 91.9% in China in March 2020 ( Wang et al, 2021 ); the highest rates of vaccine acceptance (96.9%) among the health care works were also observed in Eastern Asian countries, including China, India, the Republic of Indonesia, Singapore, Vietnam, and Bhutan ( Chew et al, 2021 ). Among factory workers, Chinese workers also reported a high behavioral intention (80.6%) to receive a COVID-19 vaccination ( Zhang and Zhou, 2021 ). Therefore, it is understandable that people's willingness to be vaccinated was as high in the improved conditions as in the conventional opt-out condition.…”
Section: Discussionmentioning
confidence: 99%
“…Risk exaggerators and vaccine-specific risk perceivers, who accounted for approximately 60% of our sample, reported the lowest willingness to be vaccinated. Recent studies have shown the association between perceived risk of COVID-19 and behavior in response to it, such as social distancing ( Barrios and Hochberg, 2020 ; Xie et al, 2020 ), hand washing ( Abdelrahman, 2022 ; Wise et al, 2020 ), panic purchasing ( Zhang and Zhou, 2021 ), as well as vaccination ( Caserotti et al, 2021 ; Karlsson et al, 2021 ). Although the intention to accept the vaccine increased as risk perception of the disease increased, risk perception of the vaccine could weaken that intention at the same time ( Freimuth et al, 2017 ; Liu and Yang, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Government forces should enhance public awareness of the epidemic trend through news and other means, publicize the role of social distancing in reducing infection, and encourage people to observe social distancing voluntarily [7]. Moreover, these factors also affect the behavioral mechanism of the public's own cognition for social distancing obedience [9,10]. Based on the previously conducted studies, several scholars applied advanced analytical approaches (e.g., a continuous infection model) and concluded that both school management and future urban development need to strengthen the management of social distancing, putting forward suggestions to enhance the governance to achieve the effect of restraining the spread of the pandemic [11,12].…”
Section: Introductionmentioning
confidence: 99%